Identification Morphology of Bamboo, and Traditional Use in Gorontalo - Febriyanti Febriyanti; Novri Youla Kandowangko; Jusna Ahmad (Jurnal Biodjati, 2023)
Bamboo is a versatile plant that has many benefits in the lives of the people of Gorontalo. This research aims to provide taxonomic information on bamboo species in Gorontalo Province, including variations in morphological characters and phenetic relationships of bamboo, as well as information on the traditional use of bamboo. The method used in this research is exploration and interviews. Exploration was carried out to collect information on bamboo taxonomy, while interviews were conducted to find out the use of bamboo by the Gorontalo Community. The research data obtained was then analyzed descriptively to describe and interpret data on morphological variations, phenetic relationships and traditional benefits of the various types of bamboo obtained. Based on the research results, it was obtained that 13 types of bamboo are distributed in Gorontalo which show the unique morphological variations of the varieties which are divided into four genera, namely the genus Gigantochloa has distinctive morphological characteristics on the waxy surface of the stem, the Bambusa genus with characteristic shiny, smooth stems, the Dendrocalamus genus has the largest diameter and stem wall thickness, the genus Schizostachyum has the same morphological characteristics of stem segments and branch lengths. Based on the analysis of phenetic relationships, two main clusters were formed with a similarity value of 61.2%. In terms of traditional uses, it was recorded in this research that most bamboo is used as building construction materials, food sources, traditional medicine, materials for traditional ceremonies, handicrafts, and ornamental plants, as a tool designedto help people's livelihoods and ecological functions. This research also provides the first record of the morphological characteristics and use of each type of bamboo in Gorontalo which can be used for future bamboo breeding and conservation projects.